Economic evaluation of antimicrobial resistance in curable sexually transmitted infections; a systematic review and a case study. - Oluseyi Ayinde; Jonathan D C Ross; Louise Jackson (PLoS ONE, 2023)
Objective To provide a summary of the economic and methodological evidence on capturing antimicrobial resistance (AMR) associated costs for curable sexually transmitted infections (STIs). To explore approaches for incorporating the cost of AMR within an economic model evaluating different treatment strategies for gonorrhoea, as a case study. Methods A systematic review protocol was registered on PROSPERO (CRD42022298232). MEDLINE, EMBASE, CINAHL, Cochrane Library, International Health Technology Assessment Database, National Health Service Economic Evaluation Database, and EconLit databases were searched up to August 2022. Included studies were analysed, quality assessed and findings synthesised narratively. Additionally, an economic evaluation which incorporated AMR was undertaken using a decision tree model and primary data from a randomised clinical trial comparing gentamicin therapy with standard treatment (ceftriaxone). AMR was incorporated into the evaluation using three approaches-integrating the additional costs of treating resistant infections, conducting a threshold analysis, and accounting for the societal cost of resistance for the antibiotic consumed. Results Twelve studies were included in the systematic review with the majority focussed on AMR in gonorrhoea. The cost of ceftriaxone resistant gonorrhoea and the cost of ceftriaxone sparing strategies were significant and related to the direct medical costs from persistent gonorrhoea infections, sequelae of untreated infections, gonorrhoea attributable-HIV transmission and AMR testing. However, AMR definition, the collection and incorporation of AMR associated costs, and the perspectives adopted were inconsistent or limited. Using the review findings, different approaches were explored for incorporating AMR into an economic evaluation comparing gentamicin to ceftriaxone for gonorrhoea treatment. Although the initial analysis showed that ceftriaxone was the cheaper treatment, gentamicin became cost-neutral if the clinical efficacy of ceftriaxone reduced from 98% to 92%. By incorporating societal costs of antibiotic use, gentamicin became cost-neutral if the cost of ceftriaxone treatment increased from £4.60 to £8.44 per patient. Conclusions Inclusion of AMR into economic evaluations may substantially influence estimates of cost-effectiveness and affect subsequent treatment recommendations for gonorrhoea and other STIs. However, robust data on the cost of AMR and a standardised approach for conducting economic evaluations for STI treatment which incorporate AMR are lacking, and requires further developmental research.